"Let's Boogie": FEASIBILITY OF A DANCE INTERVENTION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE. Issue 5 (September 2019) - Wshah, Adnan; Butler, Stacey; Patterson, Kara; Goldstein, Roger; Brooks, Dina
Abstract : Purpose: Exercise is an effective treatment for individuals with chronic obstructive pulmonary disease (COPD); however, lack of adherence to exercise programs is a common barrier. Innovative approaches to exercise are needed to increase patient engagement and adherence. Dance has been shown to benefit populations with neurological conditions. The aim of our study was to investigate the feasibility of a dance intervention in individuals with COPD. Methods: Twenty individuals with COPD participated in a 1-hr dance class delivered twice a week for 8 wk. The primary outcome measure of the study was the feasibility determined by enrollment rate, attendance rate, adverse events, and participant satisfaction. Secondary outcomes included functional capacity, balance, anxiety and depression, steps count, and health-related quality of life. Results: Of the 47 individuals approached, 37 (79%) were interested in the program and 23 (49%) consented to participate and 20 completed the program with no adverse events and a mean attendance rate of 78%. The mean age ± SD of the participants was 73.4 ± 7.6 yr and 70% were females. Participant satisfaction with the program was high and significant improvements were achieved in the 6-min walk test ( P = .03), Balance Evaluation Systems Test (BESTest) ( P < .01), Chronic Respiratory Disease Questionnaire ( P = .001), and the Activities-specific Balance Confidence scale ( P = .007). Conclusion: Dance is an enjoyable, safe, and feasible way to exercise for those with COPD. This pilot study will inform the design of a larger randomized controlled trial to determine effectiveness of dance on exercise capacity, balance, and quality of life for people with COPD. Abstract : Supplemental Digital Content is Available in the Text.Innovative rehabilitation approaches are needed to increase engagement and motivation to exercise among people with chronic obstructive pulmonary disease. We investigated the feasibility of a dance program delivered twice a week for 8 wk. Twenty participants participated in a dance program and results demonstrated that dance is a safe and feasible way to exercise.